Experimental study on improving μ- WEDM and μ-EDM of doped silicon by temporary metallic coating - Saleh, Tanveer; Rasheed, Aous Naji; Abdul Muthalif, Asan Gani (Springer, 2015)
Wire electro-discharges machining (WEDM) is a variant of electro-discharge machining (EDM) based method for non-contact machining that uses wire as the machining tool. Micro-EDMing/micro-WEDMing (where discharge energy is very low and tool size in micrometer range) operation of silicon (Si) can achieve features with very complex shapes, which have many useful applications in microelectro-mechanical system (MEMS). However, Si is a semiconductor material with high resistivity, and it is difficult to create electrical sparks during μ- WEDM/μ-EDM process. Thus, the machining of Si can be enhanced if it is possible to increase the conductivity of this semiconductor. This study aims to develop and characterize the process of improved μ-WEDM and μ-EDM of Si by temporarily coating Si with a high conductive metal (gold in this study). Micro-WEDM process stability was found to be improved (~100× for different machining condition) if coated Si wafer is used as compared to uncoated Si workpiece. Material removal rate (MRR) was also found to be increased by a good margin (~30 % average) for coated Si wafer. Machined slots were found to be more uniform though kerf width was slightly larger for coated Si wafer. In case of μ-EDM operation, goldcoated Si also enhanced the machining as compared to uncoated Si. In this case, MRR was increased by up to seven times for coated samples. Overall, this new method of μ-WEDM and μ- EDM technique of polished Si wafer has been found to be more efficient and useful. Removal of the conductive coating without damaging the substrate is a challenge for this process, which was carried out successfully by selective etching method.